(2x-8)+(9x+1)=

Simple and best practice solution for (2x-8)+(9x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-8)+(9x+1)= equation:


Simplifying
(2x + -8) + (9x + 1) = 0

Reorder the terms:
(-8 + 2x) + (9x + 1) = 0

Remove parenthesis around (-8 + 2x)
-8 + 2x + (9x + 1) = 0

Reorder the terms:
-8 + 2x + (1 + 9x) = 0

Remove parenthesis around (1 + 9x)
-8 + 2x + 1 + 9x = 0

Reorder the terms:
-8 + 1 + 2x + 9x = 0

Combine like terms: -8 + 1 = -7
-7 + 2x + 9x = 0

Combine like terms: 2x + 9x = 11x
-7 + 11x = 0

Solving
-7 + 11x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 11x = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 11x = 0 + 7
11x = 0 + 7

Combine like terms: 0 + 7 = 7
11x = 7

Divide each side by '11'.
x = 0.6363636364

Simplifying
x = 0.6363636364

See similar equations:

| 3-9(m+3)=9m-24 | | 3a+7b=8.9 | | 8+2b=40 | | 2w*w=200 | | 6x+2x=7 | | Y=4-3/4 | | 10/9x^4,8/3x | | 4x-8x-7=0 | | (8x+7y)+(7x+6y)= | | 4x+26=186 | | ln(9x+8)=6 | | 3x^2+14x+5=-3 | | 5=5+6r | | 3+7x=15+x | | -4-8r=84 | | 3x^2+14x-5=-3 | | 8m^3-32m=0 | | 3.28+w=18.28 | | 3.25w=48.75 | | P=21-6.25-(-10) | | -6/-7 | | Z-19.51=3.51 | | 3x+8+5x+4y=5x-20 | | 4y-2=2(y+14) | | a^4b^7-a^3b^2+a^2b^6-a^2b^2= | | 117=5+7m | | 6.82+z=22.82 | | 3(y+3)5=2y+3 | | (4/9)^-1.5 | | 18x+90=15x-1 | | 4x+16=92 | | 3x+y-11=0 |

Equations solver categories